Complex therapy of patients with postviral syndrome and chronic fatigue syndrome - A. S. Karabaeva (Лечащий Врач, 2023)
After suffering a new coronavirus infection COVID-19, patients face a number of disorders, the leading of which is asthenia. The purpose of our research was to study the effectiveness and safety of the use of the new biologically active complex in the rehabilitation of patients with chronic fatigue syndrome and postcovid syndrome. 25 patients who underwent COVID-19 during the two months preceding their participation in the trial were examined. The age of patients is from 20 to 60 years. All participants complained of fatigue, weakness, lethargy, decreased performance, intolerance to high mental loads, sleep disorders. The biologically active complex was prescribed to patients 1 capsule 2 times a day for 1 month on an outpatient basis. Before and after taking of biologically active complex, all patients were assessed for ALT, AST, creatinine, urea, C-reactive protein levels, as well as an assessment of chronic fatigue syndrome on the FAS scale. After taking the biologically active complex, the blood test indices in all patients returned to normal, which indicates the relief of inflammatory processes. In two patients with initially reduced hemoglobin, an increase in the parameter to the norm was recorded. All patients noted an improvement in their physical and mental state, which is characterized by a decrease in FAS scores. None of the study participants observed any adverse reactions during the intake. There were no cases of decompensation of concomitant diseases. Biologically active food supplement should be prescribed to patients with chronic fatigue syndrome and post-ovoid syndrome. The complex has good safety and portability.